Dewey in the World of Experiential Education. Issue 158 (16th April 2018) - Beard, Colin
Abstract: This chapter considers whether John Dewey's writings about experiential education are relevant to modern‐day conceptions of adult experiential learning. It highlights how some of the threads of Dewey's thinking are still pertinent, but much more complex.